2024
DOI: 10.1515/mt-2023-0237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IP-TIG welding parameters on weld bead geometry, tensile properties, and microstructure of Ti6Al4V alloy joints

Vaithiyanathan Vijayakumar,
Tushar Sonar,
Sivamaran Venkatesan
et al.

Abstract: The primary aim of this study is to analyze the influence of inter-pulse tungsten inert gas (IP-TIG) welding parameters (peak current, inter-pulse current, and inter-pulse frequency) on weld bead geometry, tensile properties, and microstructure of Ti6Al4V alloy joints for gas turbine applications. IP-TIG welding principally featured by magnetic arc constriction and pulsing was employed to overcome the high heat input problems in TIG welding of thin Ti6Al4V alloy sheets such as wider bead and HAZ, coarsening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Wan et al find that the tensile strength (TS) and elongation (EL) could be improved using the optimized weld shape [7]; the TS and EL of the welded 2219-T8 aluminium alloys were enhanced by 70 % and 4 %, respectively. Vijayakumar et al [8] presented that the peak current of 50 A, inter-pulse current of 30 A, and inter-pulse frequency of 20 kHz could be used to improve the characteristics of the IP-TIG welded Ti6Al4V alloy. The RSM model of the joint strength was developed for the IN-718 weld by Sonar et al [9], who found that the developed weld exhibited 32 % higher strength and superior corrosion resistance than TIG ones.…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al find that the tensile strength (TS) and elongation (EL) could be improved using the optimized weld shape [7]; the TS and EL of the welded 2219-T8 aluminium alloys were enhanced by 70 % and 4 %, respectively. Vijayakumar et al [8] presented that the peak current of 50 A, inter-pulse current of 30 A, and inter-pulse frequency of 20 kHz could be used to improve the characteristics of the IP-TIG welded Ti6Al4V alloy. The RSM model of the joint strength was developed for the IN-718 weld by Sonar et al [9], who found that the developed weld exhibited 32 % higher strength and superior corrosion resistance than TIG ones.…”
Section: Introductionmentioning
confidence: 99%